(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, scientific research studies various types of systematic objects, from structural objects to self-developing complex systems that are mastered at the current stage of civilization development. Today, the effective use of scientific achievements is gaining priority in social development, the well-being of society and the satisfaction of human needs. Also, special attention is paid to the tasks of forming a high appreciation of science and educating people who respect science in society.